(untitled) (Texas Journal of Multidisciplinary Studies, 2022)
The article describes the foreign experience of Islamic financial organizations. In particular, the article discusses the current state of Islamic financial indicators of the leading countries in the field of Islamic finance, the specific features of the activities of Islamic financial organizations in the CIS countries are shown.